Dokumentasi budaya benda suku kaum Brunei di Sabah - Asmiaty Amat; Lokman Abdul Samad; Awang Azman Awang Pawi; Saidatul Nornis Hj. Mahali; Budianto Mohd Tamring; Siti Zuraiyni Yassin (Universiti Malaysia Sabah, 2010)
NO ABSTRACT